2008
DOI: 10.1242/jcs.034876
|View full text |Cite
|
Sign up to set email alerts
|

The nuclear lamina promotes telomere aggregation and centromere peripheral localization during senescence of human mesenchymal stem cells

Abstract: Ex vivo, human mesenchymal stem cells (hMSCs) undergo spontaneous cellular senescence after a limited number of cell divisions. Intranuclear structures of the nuclear lamina were formed in senescent hMSCs, which are identified by the presence of Hayflick-senescence-associated factors. Notably, spatial changes in lamina shape were observed before the Hayflick senescence-associated factors, suggesting that the lamina morphology can be used as an early marker to identify senescent cells. Here, we applied quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
84
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 53 publications
5
84
1
1
Order By: Relevance
“…While our findings suggest that telomere integrity is maintained in HGPS cells, other laboratories have reported that DNA damage occurs at telomeres during normal cellular senescence and during progerin-induced premature senescence (34,35). These findings are based on the presence of telomere aggregates that are associated with the nuclear lamina and with ␥H2AX foci.…”
Section: Resultscontrasting
confidence: 40%
See 1 more Smart Citation
“…While our findings suggest that telomere integrity is maintained in HGPS cells, other laboratories have reported that DNA damage occurs at telomeres during normal cellular senescence and during progerin-induced premature senescence (34,35). These findings are based on the presence of telomere aggregates that are associated with the nuclear lamina and with ␥H2AX foci.…”
Section: Resultscontrasting
confidence: 40%
“…Moreover, hTERT does not protect against progerin-induced aberrant nuclear shape and DNA damage (48). DNA damage at telomeres has been reported in cells undergoing replicative senescence and in cells undergoing progerin-induced premature senescence (34,35). In these studies, telomere dysfunction is reflected by the presence of telomere aggregates that are associated with the nuclear lamina and with ␥H2AX foci.…”
Section: Discussionmentioning
confidence: 99%
“…The most prominent is formation of the senescence-associated heterochromatic foci [38]. Second is distorted organization of the nuclear lamina [5,39], such as downregulation of lamin B1 [40], which leads to the permeabilization of the nuclear envelope. It causes a loss of chromatin from the nucleus to the cytoplasm, together with a progressive decrease in histone content [41].…”
Section: Discussionmentioning
confidence: 99%
“…One of those changes is the accumulation of lysosomal enzyme β-galactosidase at pH = 6.0 (senescence-associated β-galactosidase/SA-β-Gal/SABG), whose activity is associated with cell senescence in vitro [3,4]. The process of cellular senescence refers to irreversible growth arrest, which is followed by changes in nuclear factors [5]. Although SA-β-Gal is widely used as a biomarker for detecting aging and senescence in stem cells in vitro [6], the proper identification of senescent cells is still insufficient and cell-based methods for identification of those cells are not quantitative [7].…”
Section: Introductionmentioning
confidence: 99%
“…This meticulous organization has functional relevance to the cell, assuring proper gene expression, replication, and genome stability (18). Diverse biological processes, such as DNA repair (19), senescence (20), apoptosis (21), and transformation (22) are associated with specific nuclear protein location patterns. Conversely, mislocalization of nuclear proteins, due to mutations, is associated with specific diseases, such as laminopathies, progeroid syndromes, and cancer (23,24).…”
mentioning
confidence: 99%